La dislalia y su incidencia en el aprendizaje de la lectoescritura, en los niños de segundo año de educación general básica de la escuela Miguel Riofrío en la ciudad de Loja, período 2018-2019. - Ramirez Cabrera, Jose Antonio (2019)
The present research work nominated: The Dislalia and its Incidence in the Learning of the Literacy, in the children of second year of General Basic Education of the Miguel Riofrio School in the city of Loja, period 2018-2019, raised as general objective: plan of activities for the dislalia that contribute to improve the learning of the reading, in the children of second year of general basic education of the school Miguel Riofrio. In the study, 26 children, 3 parents and 3 teachers from the institution mentioned in the second year of General Basic Education were defined as study population. It is a social scientific research of a descriptive nature with quantitative-qualitative approach. The methods used are: scientific, qualitative and synthetic analytical, for the process of information collection the following instruments are prioritized, techniques, such as: interviews prepared by the author and parents and teachers of the institution, logotype of Fernández Gómez logopédica , 2014, observation guide and battery of phonological awareness and initial reading of Dr. Rufina Pearson, 2014, applied to children of second year parallel "c". The results allowed to conclude that the dislalia in the second year students is of an evolutionary and pedagogical type and influences the learning moment of the reading, it is recommended: that the Director direct the methodological preparation and teacher training.